2005
DOI: 10.1002/mawe.200400856
|View full text |Cite
|
Sign up to set email alerts
|

Forging of Mg-Alloys AZ31 and AZ80

Abstract: Mg-wrought alloys recently became an engineer material of constantly increasing interest. The mechanical properties of extruded Mg-feedstock of the alloys AZ80 and AZ31 indicate their suitability for automotive applications in form of high-quality forgings. Therefore a detailed knowledge about the forming behaviour is of particular importance. In order to compare mechanical properties of available Mg-feedstock qualities compression tests at room temperature have been carried out by applying batches of AZ31-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The surface film of Alcontaining alloys contains a mixture of MgO and Al 2 O 3 or Mg(OH) 2 and Al(OH) 3 . The presence of Al in the passive layer ameliorates its protective behavior [63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface film of Alcontaining alloys contains a mixture of MgO and Al 2 O 3 or Mg(OH) 2 and Al(OH) 3 . The presence of Al in the passive layer ameliorates its protective behavior [63][64][65][66].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they exhibit electromagnetic wave shielding, stiffness, heat/creeping resistance, surface quality, formability, energy absorption, strength, and high fracture elongation in power-train components, where large die-cast components are used in the automotive, aerospace and electronic industries [1][2][3][4][5][6][7]. To increase its applications, Agnewa and Nie [8] suggested the following four major areas of research: (i) use of the computational materials science and engineering approaches in alloy development including thermodynamic and first-principles modeling; (ii) mechanistic understanding and development of creep-resistant casting alloys; (iii) mechanistic understanding and modeling of deformation, including mechanical twinning and dynamic recrystallization; and (iv) texture modification via alloying and processing, particularly strip casting of the sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Similar investigations have also been conducted by Viehweger et al [45], they studied the influence of cast versus extruded stock material on the warm forming behavior of AZ80 and AZ31. The alloys were analyzed using upsetting tests, microstructural analysis and concluding isothermal forging trials with simple testing geometries.…”
Section: Az80mentioning
confidence: 52%
“…In a comparison of extruded and continuously cast AZ31 and AZ80 presented by Viehweger et al [45], no differences in the forging behavior were observed. While the flow curves (compression tests at 300, 350, 400 and 450 • C, with 0.1, 1 and 10 s −1 ) and final microstructures varied in the diverse samples and alloys, the forging of simple geometries, using a punch speed of 1 to 40 mm s −1 at various temperatures, was consistently successful.…”
Section: Az31mentioning
confidence: 82%
“…[1][2][3] The AZ80 alloy has been a well-known commercial magnesium alloy, due to its high strength and low price. [4][5][6] Some studies of AZ80 alloy have also been reported, including its microstructure and mechanical property, 7) creep behavior, 8,9) forging 10) and welding. 11) However, the AZ80 Mg alloy still has some drawbacks, such as the poor ductility, low thermal conductivity and resistivity, etc.…”
Section: Introductionmentioning
confidence: 99%